2001
DOI: 10.1071/ea00094
|View full text |Cite
|
Sign up to set email alerts
|

Post-weaning growth of cattle in northern New South Wales. 2. Growth pathways of steers

Abstract: Abstract. This paper describes the post-weaning growth of Bos taurus and Bos taurus × Bos indicus-derived steers grazing temperate perennial pasture in northern New South Wales. These cattle were either autumn weaners from spring-calving herds in summer rainfall environments, or summer weaners from autumn-calving herds in winter rainfall environments. Autumn weaners were grown out on 3 pasture systems: (i) pasture only (P1), (ii) pasture supplemented in late winter-early spring with formulated pellets of high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Dicker et al (1) demonstrated that supplementing steers backgrounded on pasture generally increases post‐weaning ADG (1.14 vs. 1.69 lb) and reduces the period to feedlot entry compared to steers backgrounded on pasture without supplement. Our study provided similar results since animals on higher nutritive value pasture and those fed higher levels of supplementation had an increased ADG (0.40 vs. 3.21 lb).…”
Section: Comparison To Other Researchmentioning
confidence: 99%
“…Dicker et al (1) demonstrated that supplementing steers backgrounded on pasture generally increases post‐weaning ADG (1.14 vs. 1.69 lb) and reduces the period to feedlot entry compared to steers backgrounded on pasture without supplement. Our study provided similar results since animals on higher nutritive value pasture and those fed higher levels of supplementation had an increased ADG (0.40 vs. 3.21 lb).…”
Section: Comparison To Other Researchmentioning
confidence: 99%
“…Differences between the expected and observed LWGs at the end of first winter were probably due to favourable weather conditions during winter, with higher temperatures and lower rainfall than in an average year. Previous studies have reported similar differences in LW at the end of the growth phase for steers reared on different postweaning growth pathways (Ridenour et al 1982;Sainz et al 1995;Dicker et al 2001;Robinson et al 2001;Loken et al 2009).…”
Section: Winter-growth and Compensatory Phasementioning
confidence: 71%
“…However, most of the research has been focussed on finishing systems, without considering the effects of winter nutrition during rearing on subsequent finishing performance. The impact of improvement in nutritional status immediately after weaning on animal performance, tissuedeposition pattern and feed conversion ratio (FCR) during the finishing phase has been widely reported (Parks 1982;Owens et al 1995;Dicker et al 2001;Robinson et al 2001;Purchas et al 2002). Therefore, better nutrition throughout the inclusion of the feedlot at an early stage can influence the rate and pattern of animal tissue deposition, and modify the type of final product obtained.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies did not investigate the feedlotfinishing growth performance and carcass quality of the animals. Backgrounding diet and weight gain influence subsequent finishing feed intake and growth performance, but results have been inconsistent (9)(10)(11). Reuter and Beck (12) reported that finishing average daily weight gain (ADG) and dry matter intake (DMI) decreased as backgrounding ADG increased in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…However, the difference may not persist when animals are finished in the feedlot before slaughter ( 23 , 24 ). While some studies have evaluated the impact of the finishing diets on carcass quality traits ( 25 , 26 ), fewer studies have examined the effect of backgrounding on finishing growth performance and carcass quality ( 10 , 15 , 27 ). In addition, there is an existing knowledge gap on the feedlot growth performance of tropical beef cattle backgrounded on grass pastures augmented with desmanthus.…”
Section: Introductionmentioning
confidence: 99%